Palace of Prince Esterházy at Mariahilf - Zutz, Josef (engraver):::Creator::::::::::::; Mollo, Tranquillo, 1767-1827. Wiens vorzüglichste Gebäude und Monumente:::Contributor:::::::::::: (Vienna; Austria; chez Tranquillo Mollo)
Color engraving with view of the Palais Esterházy in Mariahilf, Vienna, Austria